2009
DOI: 10.2215/cjn.03790808
|View full text |Cite
|
Sign up to set email alerts
|

Cinacalcet Lowers Serum Alkaline Phosphatase in Maintenance Hemodialysis Patients

Abstract: Background and objectives: Studies suggest an association between elevated serum alkaline phosphatase (AP) and increased mortality in hemodialysis patients, but the effect of existing therapies on AP is not fully understood. We assessed the effects of cinacalcet on AP in a secondary analysis of controlled trial data.Design, setting, participants, & measurements: This was a post hoc analysis of data from three 26-wk randomized, double-blind, placebo-controlled, phase 3 trials and a 26-wk double-blind, placebo-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 33 publications
1
23
1
Order By: Relevance
“…In contrast, our findings suggest that, when examined as a baseline measurement, elevated ALP is associated with increased mortality in PD patients, even within high-normal ranges. Given that several therapeutic interventions (activated vitamin D and calcimimetics, for example) have been shown to lower ALP concentrations, further study is needed to determine if a reduction in serum ALP leads to improved outcomes (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, our findings suggest that, when examined as a baseline measurement, elevated ALP is associated with increased mortality in PD patients, even within high-normal ranges. Given that several therapeutic interventions (activated vitamin D and calcimimetics, for example) have been shown to lower ALP concentrations, further study is needed to determine if a reduction in serum ALP leads to improved outcomes (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…For this study, data on oral medications including calcimimetics or phosphorus binders were not available. The calcimimetic cinacalcet became available in the United States during the last few months of this cohort [26,27]. Hence, the cohort is practically a precalcimimetic cohort.…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, as shown in Table 4, the level of circulating AP can be effectively decreased by active vitamin D products (51,52,76 -78) (and possibly also calcimimetics [79], further description of which is beyond the scope of this focused review paper). Indeed a recent meta-analysis, which questioned the PTH lowering effect of active vitamin D analogs, showed that these agents can decrease serum AP effectively (80).…”
Section: Vitamin D and Alkaline Phosphatasementioning
confidence: 99%